External Locus Of Control, Financial Attitude, Dan Financial Management Behavior - Mentari Clara Dewanti; Daisy Marthina Rosyanti; Fani Khoirotunnisa (JISAMAR (Journal of Information System, Applied, Management, Accounting and Research), 2022)
Generation Z's behavior in consuming goods and services has a tendency to a consumptive lifestyle, which can disrupt financial stability. Therefore, skills in managing finances must be possessed by Generation Z. Financial Management Behavior must be understood because the ability to manage finances helps to avoid a consumptive lifestyle. The focus of this study is to examine the effect of financial attitude on financial management behavior mediated by external locus of control on the consumption pattern of Generation Z, who in this study are students of the Management Department, Faculty of Economics and Business at UPN "Veteran" East Java. The number of samples in this study is 325. This study used the PLS-based Structural Equation Modeling (SEM) method. Based on the results of the study, it was found that Financial Attitude has a positive influence on Financial Management Behavior, and external locus of control has a partial effect on the two variables studied.